2005
DOI: 10.1021/ol050780m
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Bond Isosteres:  Ester or (E)-Alkene in the Backbone of the Collagen Triple Helix

Abstract: [structure: see text] Collagen is the most abundant protein in animals. Interstrand N-H...O=C hydrogen bonds between backbone amide groups form a ladder in the middle of the collagen triple helix. Isosteric replacement of the hydrogen-bond-donating amide with an ester or (E)-alkene markedly decreases the conformational stability of the triple helix. Thus, this recurring hydrogen bond is critical to the structural integrity of collagen. In this context, an ester isostere confers more stability than does an (E)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 26 publications
1
97
0
Order By: Relevance
“…General Protocol: The appropriate Boc-Xaa-Gly-OBn derivative (11) or (16) 79 (52.5 mmol) was dissolved in 4 N HCl in dioxane (700 mL) under Ar(g) and stirred for 2 h. The resulting solution was concentrated under reduced pressure, dried under high vacuum and the residue dissolved in anhydrous CH 2 Cl 2 (800 mL) under Ar(g). The appropriate 4-chloroproline derivative (7) or (8) …”
Section: Pybrop Couplingsmentioning
confidence: 99%
“…General Protocol: The appropriate Boc-Xaa-Gly-OBn derivative (11) or (16) 79 (52.5 mmol) was dissolved in 4 N HCl in dioxane (700 mL) under Ar(g) and stirred for 2 h. The resulting solution was concentrated under reduced pressure, dried under high vacuum and the residue dissolved in anhydrous CH 2 Cl 2 (800 mL) under Ar(g). The appropriate 4-chloroproline derivative (7) or (8) …”
Section: Pybrop Couplingsmentioning
confidence: 99%
“…Likewise, proteins containing a cis-peptide bond can be stabilized by constrained amides or isosteres (21)(22)(23). The utility of these substitutions is limited, however, by the difficulty of modifying the backbone of proteins as well as concomitant effects on structure and function (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…It was revealed that vaccine efficacy does not only depend on the biochemical composition of the immunogens (vaccine constructs) but also their morphological properties, such as particle size, plays a role in the induction of immune response [50,51]. There are reports that vaccines delivered in the form of particulate: (i) are likely to be uptake by APCs for immune processing [52]; (ii) protects antigen from enzymatic degradation; and (iii) large particulates can act as depots (i.e.…”
Section: Formulation Into Nanoparticlesmentioning
confidence: 99%
“…There are reports that vaccines delivered in the form of particulate: (i) are likely to be uptake by APCs for immune processing [52]; (ii) protects antigen from enzymatic degradation; and (iii) large particulates can act as depots (i.e. trapping antigen and therefore slowly presents the antigen to immune cells) [53] while smaller ones (<200 nm) are readily transported through the lymphatic system [51,52], where many immune cells reside. These discoveries resulted to growing interest into the development of vaccines with well-defined particle sizes [33].…”
Section: Formulation Into Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation